Leadership Under Islamic Norms (Al Imamah fill Islam) - Moh. Rifai (Social Sciences, Humanities and Education Journal (SHE Journal), 2020)
Based on the expert opinions, a leadership was a governance which carried out by someone (individual) including institutions based on deliberation that gave a consensus decisions in the form of right and obligation which must be done as the mandate. Another argument said that a leadership was a society servants (al imamu huwa ngabdu qoumin). In fact, the country that was not Islamic state (under Islamic norms) there was different meaning of a leadership here. A leader would develop based on the basic foundations (norms) of each countries including have different patterns which be expanded by each government systems of its country. For the example, the Republic of Indonesia which embraced Presidential systems with Trias politica models (The typical division is into three branches: a legislature, an executive, and a judiciary) that have its primary tasks and functions. When these branches were not harmonious, it would made imbalance nuances and mutual suspicion among the government institutions.